2007
DOI: 10.1074/jbc.m702639200
|View full text |Cite
|
Sign up to set email alerts
|

Development of Cytosolic Hypoxia and Hypoxia-inducible Factor Stabilization Are Facilitated by Aquaporin-1 Expression

Abstract: O 2 is essential for aerobic life, and the classic view is that it diffuses freely across the plasma membrane. However, measurements of O 2 permeability of lipid bilayers have indicated that it is much lower than previously thought, and therefore, the existence of membrane O 2 channels has been suggested. We hypothesized that, besides its role as a water channel, aquaporin-1 (AQP-1) could also work as an O 2 transporter, because this transmembrane protein appears to be CO 2 -permeable and is highly expressed i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
85
0
2

Year Published

2008
2008
2016
2016

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 113 publications
(91 citation statements)
references
References 44 publications
(58 reference statements)
4
85
0
2
Order By: Relevance
“…In this study, cellular oxygen fluxes were not directly measured because of the technical difficulties as authors described. However, the LopezBarneo study strongly indicated that AQP1 is permeable for oxygen and thus could facilitate oxygen uptake into cells [27]. In support of such a suggestion, Ivanov II et al reported that the two AQP channel blockers, mercury chloride (HgCl 2 ) and p-chloromercuribenzoate (PCMB), dose-dependently inhibited oxygen absorption by erythrocytes [28].…”
Section: Oxygen Utilizationmentioning
confidence: 71%
“…In this study, cellular oxygen fluxes were not directly measured because of the technical difficulties as authors described. However, the LopezBarneo study strongly indicated that AQP1 is permeable for oxygen and thus could facilitate oxygen uptake into cells [27]. In support of such a suggestion, Ivanov II et al reported that the two AQP channel blockers, mercury chloride (HgCl 2 ) and p-chloromercuribenzoate (PCMB), dose-dependently inhibited oxygen absorption by erythrocytes [28].…”
Section: Oxygen Utilizationmentioning
confidence: 71%
“…Since CORM-2 is highly lipophilic, it will diffuse rapidly across the membrane and might be expected to deliver CO to intracellular motifs of membrane proteins at much higher concentrations than can be achieved with membrane diffusion of CO gas. Of course, there is also the possibility that CO, like CO 2 [42] and O 2 [43], requires a specific permeation pathway, which is absent in these cells. Such an idea is supported by recent experiments in Escherichia coli, which show that CORM-3, the water-soluble CO donor molecule, is taken up and exerts CO-specific growth inhibitory effects, whilst the addition of dissolved CO into the growth medium is without effect [44].…”
Section: Discussionmentioning
confidence: 99%
“…[104][105][106][107] In addition, hypoxia-inducible trans-cription factors, HIF-1a or 2a, may take part in the proliferation mediated by AQPs. We have shown that stable overexpression of AQP1, 3 and 5 increases the stability of HIF-2a during chronic exposure to hypoxia 108,109 thereby increasing the expression of many genes implicated in activities relevant for tumor growth, such as glucose uptake and metabolism, angiogenesis, cell proliferation and apoptosis. 110 We also reported that AQP1 can be induced in hypoxia by HIF-1a, 111 thus sustaining an auto-cycle effect that would contribute to cell proliferation.…”
Section: Cross-talk Between Transcription Factors Cytokines and Aqpsmentioning
confidence: 99%
“…1,58,136 However, it is important to note that expression levels of specific AQPs have been demonstrated to account for higher water transport and fluid clearance from specific compartments not only under the pathophysiological conditions of cancer, but also under many other normal physiological conditions that imply changes in the hydraulic conductivity of tissues and organs (such as those that occur in the lung, kidney, skin or brain during fetal development and organ regeneration). 58,[137][138][139] Upregulation of AQP expression has been observed under stimuli such as dehydration in the kidney leading to overexpression of AQP2 and AQP3, [140][141][142] or hypoxia in the lung producing overexpression of AQP1 108,111,142,143 and in none of these cases have the proposals to explain AQPs overexpression been at all related to tumor proliferation. More recent studies have demonstrated involvement of AQP1 in the differentiation of stem-like cells in rat bile duct formation, 144 development of human corneal keratocytes 145 and renewal of limbal basal epithelium from a corneal epithelial stem cell niche, 146 all important roles associated with cell proliferation and differentiation.…”
Section: Apoptosis and Aqpsmentioning
confidence: 99%